The Functions of Biochar and Arbuscular Mycorrhizal Fungi to Increasing the Yield of Glutinous corn on sub-optimal land in a sustainability - Rosnina Rosnina (Department of Crop Science, Faculty of Agriculture, Andalas University, 2022)
This study aims to determine the role of biochar and mycorrhizal fungi in increasing soil fertility Inceptisols as suboptimal soil, which are poor in nutrients, low in carbon, and phosphorus, are suitable for planting of purple pulut corn (Zea mays ceratina Kulesh). This study used a randomized block design (RAK) with a factorial pattern of 3 replications, namely the dose of biochar (B) 0 t/h, 2 t/h, 4 t/h, and mycorrhizae (M) with a dose of 0 t/h, 0.2 t/h, 0.4 t/h. The data obtained were further tested with Duncan's multiple range test at a level of 5%. The application of biochar and mycorrhizae affected the number of leaves, days of flowering for males and females, and rows of This study aims to determine the role of rice husk biochar and mycorrhizal fungi in increasing soil fertility. Inceptisols, which are poor in nutrients, low in carbon, and phosphorus, are suitable for planting. There is an interaction in the administration of biochar 2 t/h + mycorrhiza 0.2 t/h on rows per row of purple pulut corn cobs. The application of biochar and mycorrhizae can overcome land infertility and provide the nutrients suitable for crops for supporting sustainable agriculture.